Research on Key Technologies of Traction System Based on Power Electronic Transformer - SONG Pinggang; GE Wang; ZHU Weichang (Kongzhi Yu Xinxi Jishu)
This paper proposed a main circuit structure of a new traction drive system based on power electronic transformer (PET). Compared with traditional traction drive system, the new transmission system has lighter weight and smaller size , has more flexible traction AC motor power supply mode due to hierarchical structure, and is more conducive to the use of axial control of the traction motor power supply. Based on the new traction system, power model in PET level was established, and the relationship between voltage balance and traction power of the main circuit was analyzed. It also analyzed the influence of working mode of the intermediate frequency isolation stage on traction drive characteristic, dynamic characteristics changing of inverter and motor, and the coupling control of PET and the AC speed control system. Finally, characteristics of the new traction drive system and its advantages to next generation EMU were summarized.